The Effects of Pro Forma Earnings Disclosures on Analysts' and Nonprofessional Investors' Equity Valuation Judgments - Frederickson, James R.; Miller, Jeffrey S. (The Accounting Review, 2004)
This paper presents an experiment that examines the effect of pro forma earnings disclosures on the judgments of analysts (i.e., more sophisticated investors) and nonprofessional (i.e., less sophisticated) investors. In the experiment, participants developed stock price assessments after reviewing background financial information and a current earnings announcement for a company. The earnings announcement was manipulated to report only GAAP earnings in one condition and both pro forma and GAAP earnings in the other condition. Consistent with empirical evidence, the pro forma earnings in our experiment exceeded GAAP earnings. The results indicate that nonprofessional investors who received an earnings announcement that contained both pro forma and GAAP disclosures assessed a higher stock price than did nonprofessionals who received an announcement containing only GAAP disclosures. Financial analysts' stock price judgments were not affected by the pro forma disclosures. Followup analyses suggest that analysts and nonprofessional investors used different valuation models and information processing. Analysts used well-defined valuation models, based on either earnings-multiples or cash flows, while the nonprofessional investors were more likely to use simpler, heuristic-based valuation models. The pro forma disclosure did not cause nonprofessional investors to assess a higher earnings number for determining a stock price, but rather caused nonprofessionals to perceive the earnings announcement as more favorable, which in turn caused them to convert earnings or some other performance metric into a higher stock price. This effect appears to be due to unintentional cognitive effects, rather than nonprofessionals relying on pro forma earnings information because they perceived it to be informative.